Strategi Smart Test Dalam Pembelajaran Latsar CPNS di Era Society 5.0 - Agus Suharsono; Ana Uluwiyah (Pancanaka, 2020)
An important point in community 5.0 is cross-section based on knowledge and information, thus encouraging people to be able to continue to grow and develop into active community people. The concept in society 5.0, has begun to develop in the culture of Indonesian society. There are several important indicators, including public awareness to use IT as an "enabler" in supporting work activities. This paper will provide a general description of one of the learning methods that support the realization of a culture of society 5.0 to improve the competence of training participants, through empirical studies with survey data on the CPNS Latsar Training Ministry of Finance. Based on the results of descriptive analysis, a general description is obtained that through the development of learning methods that are appropriate to the culture of society 5.0, learning objectives such as increasing the competency of participants are more easily achieved. The reason is because, the development of learning methods, in this paper uses Quizizz, according to the needs and culture of the participants which is basically 100% millennial generation. This can be concluded, that with the culture of society that has begun to shift to sociality 5.0, the government needs to innovate or breakthrough according to community needs to be more effective and efficient.